Institutional Domains, Fields of Tensions and Institutional Innovation: a Sociological Approach - Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2007)
This article explores the structural roots of institutional fields of tensions. It singles out four societal domains – bureaucratic, economic, academic, and civic – and elaborates on different doctrines, steering mechanisms and ethos prevailing in such domains. It draws on Max Weber’s concepts of “ideal types’ of politically and economically-oriented action as a theoretical predecessor of the concept of domains and institutional tensions. It also draws on Giddens’ interpretation of social structuring processes, and develops a notion of institutional learning by proposing a concept of inter-institutional learning. The recent case of developing a new nuclear power plant in Lithuania is deployed in this article inter alia as an illustration of the tensions arising between different institutional domains, as an illustration of dominance of certain principles, steeringmechanisms and ethos pertaining to particular institutional domains, e.g. bureaucratic and economic, whereas other domains such as civic are neglected or marginalized. It is also conceived as an example illuminating the opening of possible ways in the search for institutional innovations.
Keywords: social institutions; interaction; fields of tension; bureaucratness; enterpriseness; democracy; institutional inovativeness